Building a Model to Predict Sexual Assault Victimization Frequency Among Undergraduate Women - Kirwan, Mitchell (Violence against women, 2022)
Previous research has identified several factors, including sexual risk behaviors, alcohol consumption, sexual refusal assertiveness, impulse control difficulties, drinking to cope, and sex to cope, as being associated with sexual assault victimization. Data were collected from 465 adult, undergraduate women, and analyzed using structural equation modeling to determine how these variables related to one another. Results showed that together, these factors predicted 17.1% of the variance in victimization frequency. These findings may help future researchers better understand the etiology of sexual assault victimization on college campuses and prove crucial to the development of future intervention programs which reduce victimization.